Danopolonian migmatization of Mesoproterozoic sedimentary rocks in southernmost Sweden: a SIMS zircon study - Bogdanova, Svetlana; Čečys, Audrius; Bibikova, Elena; Ilyinsky, Lev S.; Taran, Ludmila (GFF, 2014)
To assess the age and origin of the metasedimentary migmatites in southernmost Sweden and their relationships with the Mesoproterozoic granitoid magmatism in the area, we have dated migmatite zircon using the secondary ion mass spectrometry U–Pb method. The studied metasedimentary migmatites, here called the No¨teboda migmatites, occur along the southwestern boundary of the 1442Ma Ta°ghusa granitoid intrusion in southeastern Ska°ne. They contain the mineral assemblage garnet þ biotite ^ muscovite þ cordierite þ sillimanite þ quartz þ plagioclase þ K-feldspar and were formed during a retrograde evolution from c. 750–7208C and 6 kbar (peak conditions) to c. 6758C and 4 kbar. Zircon is characterized by detrital cores surrounded by U-rich rims and overgrowths. Separate rounded metamorphic grains also exist. The age probability–density distribution peaks for detrital zircon are at c. 1700, 1670, 1650, 1610, 1570 and 1530 Ma. These ages suggest Gothian orogenic rocks in the present west as the most probable principal source. Sedimentation occurred after c. 1530 Ma, the age of the youngest detrital zircon, indicating the existence of a previously unknown period of Mesoproterozoic sedimentation in southernmost Sweden. A homogeneous zircon overgrowth yielded a concordant 207Pb/206Pb age of 1439 ^ 5 Ma, which dates the migmatization and is close to the age of the Ta°ghusa intrusion. We conclude that the burial of the sediments down to c. 20 km, their metamorphism and progressive migmatization took place concurrently with granitic magmatism, NE–SW compression, folding and shearing of the crust between 1460 and 1440Ma during the Danopolonian orogeny.